The Paradox of “即 (Jí)” in Tiantai Buddhism - Zhang, Yi (Religions, 2024)
The character “即 (jí)” in Chinese shares the meaning of “is”, indicating an identity or equivalence between two concepts. In this framework, one might expect the antecedent and the consequent of “即” to be identical in meaning, or at least for a term with a positive connotation not to be paired with one of negative connotation. However, in Tiantai Buddhism, many core propositions follow the structure “x 即 y”, where x is negative and y is positive, or vice versa. This suggests an identity between opposites, creating a paradoxical feature in the system. This essay argues that the paradox within Tiantai Buddhism is a veridical paradox, as defined by Quine, meaning it can be resolved in various ways and does not reflect a genuine contradiction in reality. While Western Buddhist philosophers and logicians have focused primarily on the paradoxes in Nāgārjuna’s thought, this essay demonstrates that Chinese Tiantai Buddhism offers practical resolutions to these paradoxes. The paper first explicates the paradox by examining its roots in Buddhist history, then explores responses to it. Finally, different methods for resolving the paradox are compared and evaluated.